2005
DOI: 10.1017/s095252380522401x
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field ganglion cells in macaque retinas

Abstract: To describe the wide-field ganglion cells, they were injected intracellularly with Neurobiotin using an in vitro preparation of macaque retina and labeled with streptavidin-Cy3. The retinas were then labeled with antibodies to choline acetyltransferase and other markers to indicate the depth of the dendrites within the inner plexiform layer (IPL) and analyzed by confocal microscopy. There were eight different subtypes of narrowly unistratified cells that ramified in each of the 5 strata, S1-5, including narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 34 publications
13
82
0
Order By: Relevance
“…They have branches in both sublamina a and sublamina b and a characteristic retroflexive branching pattern. Morphologically similar types have been reported in other species including primate (Yamada et al, 2005) and mouse (Weng et al, 2005). The depth of stratification in the IPL, which can be accurately visualized by confocal microscopy (Masland & Raviola, 2000), is a primary diagnostic feature to differentiate between different ganglion cell types (Watanabe & Rodieck, 1989).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…They have branches in both sublamina a and sublamina b and a characteristic retroflexive branching pattern. Morphologically similar types have been reported in other species including primate (Yamada et al, 2005) and mouse (Weng et al, 2005). The depth of stratification in the IPL, which can be accurately visualized by confocal microscopy (Masland & Raviola, 2000), is a primary diagnostic feature to differentiate between different ganglion cell types (Watanabe & Rodieck, 1989).…”
Section: Introductionsupporting
confidence: 61%
“…The number of cone bipolar cell types in the mammalian retina is usually given between 10 and 12, plus one for the rod bipolar cells (Haverkamp et al, 2003;Ghosh et al, 2004;MacNeil et al, 2004), and there is strong evidence that different bipolar cell types have different physiological properties, thus splitting the photoreceptor signals into different channels (DeVries, 2000). The number of ganglion cell types has been estimated as 13 or 14, but there is usually an unclassified remainder which could include a number of sparse or low-density cell types (Rockhill et al, 2002;Marc & Jones, 2002;Dacey et al, 2003;Yamada et al, 2005). This may boost the total number of types to between 15 and 20.…”
Section: Stratification Of the Iplmentioning
confidence: 99%
“…Furthermore, because the ratio of the RF diameter of the OFF upsilon cells to the RF diameter of OFF parasol cells is ϳ2.9, the ratio of the dendritic arbor diameter of the upsilon cells to the dendritic arbor diameter of the parasol cells is expected to also be ϳ2.9 [assuming the same ratio of the RF to the dendritic arbor diameters for both cell types (Peichl and Wassle, 1983)]. Given these constraints, the most plausible morphological candidate(s) corresponding to the upsilon cells are the smooth (Dacey, 2004) and large radiate (Yamada et al, 2005) ganglion cells recently identified in the primate retina.…”
Section: Possible Morphological Correlate Of the Upsilon Cellsmentioning
confidence: 99%
“…Based on the measured upsilon cell properties, we can speculate as to which morphological RGC type (Rodieck and Watanabe, 1993;Dacey et al, , 2005Dacey, 2004;Yamada et al, 2005) they may correspond to. Because the upsilon cells are OFF-type cells with no evidence for ON-OFF responses (i.e., no significant responses to both light intensity increments and decrements) (Fig.…”
Section: Possible Morphological Correlate Of the Upsilon Cellsmentioning
confidence: 99%
See 1 more Smart Citation